HUBUNGAN KESEJAHTERAAN PSIKOLOGIS DENGAN RESILIENSI GURU PAUD DI KECAMATAN TAMPAN KOTA PEKANBARU - Destriya Andriani; Ria Novianti; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The aim of this research is to know whether there is a relation between psychological well-being andthe resilience of PAUD teachers in Tampan District, Pekanbaru. The population in this study were PAUD teachers in Tampan Subdistrict, Pekanbaru, amounting to 76 teachers, this sample was used as many as 20 PAUD teachers taken using simple random sampling technique. The method used is Product Moment correlation to see the relationship between variables of psychological well-being and resilience of PAUD teachers. Data collection techniques used were questionnaires in the form of a likert scale. The data analysis technique uses scale trials and statistical method analysis with the SPSS program for Windows Ver. 25. Based on the results of hypothesis testing obtained there is a positive and significant relationship between psychological well-being and resilience of PAUD teachers in Tampan District, Pekanbaru. This can be seen from the correlation coefficient of rxy => 0.558 and a significant level of 0,000 <0.05. The level of relationship between psychological well-being and resilience of PAUD teachers is included in the strong category with a determinant coefficient value of 31.2%, meaning that PAUD teachers on psychological well-being have an effect of 31.2% on resilience.Key Words: Psychological Well-being, Resilience, Reaching out.